Three‐dimensional spheroid cell culture of human MSC‐derived neuron‐like cells: New in vitro model to assess magnetite nanoparticle‐induced neurotoxicity effects. Issue 7 (9th February 2022) - De Simone, Uliana; Croce, Anna Cleta; Pignatti, Patrizia; Buscaglia, Eleonora; Caloni, Francesca; Coccini, Teresa
Abstract: As nanoparticles (NPs) can access the brain and impact on CNS function, novel in vitro models for the evaluation of NPs‐induced neurotoxicity are advocated. Three‐dimensional spheroids of primary neuron‐like cells (hNLCs) of human origin have been generated, from differentiation of human umbilical cord mesenchymal stem cells (MSCs). The study evaluated Fe3 O4 NP impact on the differentiation process by applying the challenge at complete 3D hNLC spheroid formation (after 4 days, T4) or at beginning of neurogenic induction/simultaneously 3D forming (T0). Different endpoints were monitored over time (up to 10 days): spheroid growth, size, morphology, ATP, cell death, neuronal markers (β‐Tub III, MAP‐2, and NSE), NP uptake. At T0 application, a marked concentration‐ and time‐dependent cell mortality occurred: effect started early (day 2) and low concentration (1 μg/ml) and exacerbated (80% mortality) after prolonged time (day 6) and increased concentrations (50 μg/ml). ATP was strikingly affected. All neuronal markers were downregulated, and spheroid morphology altered in a concentration‐dependent manner (from ≥5 μg/ml) after day 2. Fe3 O4 NPs applied at complete 3D formation (T4) still induced adverse effects although less severe: cell mortality (20–60%) and ATP content decrease (10–40%) were observed in a concentration‐dependent manner (from ≥ 5 μg/ml). A neuronal‐specific marker effect and spheroid size reduction from 25 μg/ml without morphology alteration were evidenced. This finding provides additional information on neurotoxic effects of Fe3 O4 NPs in a new 3D hNLC spheroid model derived from MSCs that could find a consistent application as in a testing strategy serving in first step hazard identification for correct risk assessment. Abstract : Human spheroids of neuron‐like cells (hNLCs) were generated from differentiation of umbilical cord mesenchymal stem cells. When Fe3 O4 NPs were applied at beginning of neurogenic induction/simultaneously spheroid forming, marked toxicity occurred early (day2) from 5 μg/ml. Fe3 O4 NPs applied at complete spheroid formation still induced adverse effects although less severe. This finding provides additional information on neurotoxic effects of Fe3 O4 NPs in a new hNLC spheroid model that could find a consistent application as in a testing strategy serving in first step hazard.